APA Handbook of Men and Masculinities. 2016
DOI: 10.1037/14594-034
|View full text |Cite
|
Sign up to set email alerts
|

Men and psychotherapy.

Abstract: It has been well supported that men underutilize mental health services (see Chapter 31, this chapter); however, this is not due to a lack of need for such assistance (Addis & Mahalik, 2003;Cochran, 2005). In fact, men and women are equally as likely to develop a mental disorder throughout their lifetime, with men having higher rates of substance abuse and antisocial personality disorder and women being more likely to experience affective disorders (Kessler et al., 1994). Additionally, the emotional expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 90 publications
0
21
0
Order By: Relevance
“… Strokoff, Halford, and Owen (2016) conducted a review of 15 studies employing male-targeted psychological treatment approaches and identified only a single, small randomized study examining a treatment specifically tailored for men. This study investigated the use of a brief alliance-building intervention, known as gender-based motivational interviewing (GBMI), in a community-based sample of men with symptoms of anxiety and depression and no statistically significant effects were reported ( Syzdek, Addis, Green, Whorley, & Berger, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“… Strokoff, Halford, and Owen (2016) conducted a review of 15 studies employing male-targeted psychological treatment approaches and identified only a single, small randomized study examining a treatment specifically tailored for men. This study investigated the use of a brief alliance-building intervention, known as gender-based motivational interviewing (GBMI), in a community-based sample of men with symptoms of anxiety and depression and no statistically significant effects were reported ( Syzdek, Addis, Green, Whorley, & Berger, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is an emergent knowledge base of techniques for engaging male clientele (Mahalik et al, 2012; Seidler et al, 2018a; Owen et al, 2010). Across these studies, the need for appropriate psychoeducation and familiarization with therapy processes, adopting a transparent, and flexible structure to therapy, alongside a strengths-based empowerment orientation have been emphasized as male-friendly strategies (Richards & Bedi, 2015; Seidler et al, 2018a; Strokoff et al, 2016). At the same time, this does not mean therapy with men should be void of emotional exploration; indeed more masculine men have noted the importance of such interventions (Owen et al, 2010).…”
Section: Efforts To Improve Therapy For Men: Mental Health Practition...mentioning
confidence: 99%
“…We define gender competency when working with male clients in mental healthcare as reflecting the capacity to effectively demonstrate practical awareness of the interaction between masculinities and men’s mental health, via implementation of adaptations to treatment according to each man’s experience. More specifically, gender competency with men promotes viewing each man’s cultural experience as a broad, complex lived reality of plural “masculinities” that intersect and coalesce over time (Connell, 1995), which potentially contribute to his presenting problem(s), innate coping, and subsequent therapy experience and needs (Liu, 2005; Seidler et al, 2019c; Strokoff et al, 2016). Additionally, gender competency with male clients should include demonstrable evidence that practitioners recognize therapy as a pertinent context for the interaction between the client’s and practitioner’s respective gendered values, attitudes, and behaviors.…”
Section: Efforts To Improve Therapy For Men: Mental Health Practition...mentioning
confidence: 99%
“…The outdated homogenization of men fails to address the complexities of men’s mental health needs, primarily their problematic ambivalence, engagement, and mistrust with, and drop out from, mental health treatment (Johnson et al, 2012; Pederson & Vogel, 2007). In broadening the clinical perspective to understanding and integrating a masculinities framework, it follows that the male clients will be approached with an openness that supports their engagement (Strokoff, Halford, & Owen, 2016). A masculinities model is arguably the best way forward as it provides a contemporary, theoretical framework for addressing the diversity inherent in men’s mental health needs.…”
mentioning
confidence: 99%